Sustainable eating begins with youth: exploring organic food consumption intentions among young adults in Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
As Malaysia moves towards more sustainable food practices, organic food consumption has gained traction, especially among young adults. This study discusses the factors that have been found to be most significant in determining the intentions of young adults to consume organic food. The model is based on the Theory of Planned Behavior (TPB) but adds two more constructs to this framework, health consciousness and environmental concern, to explain more about the behavior. The online survey in Malaysia included Sabah and Sarawak (n = 324) was employed to gather the data based on a purposive sampling method and analysed via Partial Least Squares Structural Equation Modeling (PLS-SEM). Here, the outcomes reveal that attitude, perceived behavioral control, health consciousness, and environmental concern significantly predict intention to consume organic food, with health consciousness emerging as the strongest determinant. However, subjective norms were found to be statistically insignificant in shaping intention. These results underscore the relevance of personal health orientation and environmental values in driving organic food choices among Malaysian youth, while suggesting a diminishing role of social influence. The study offers valuable implications for policymakers, marketers, and organic food producers in crafting effective strategies that align with health-driven and eco-conscious consumer motivations.
Keywords: Organic food; Theory of Planned Behavior; health consciousness; environmental concern